The state and my happiness: Youth mental health, citizenship education and discursive contestations in contemporary Indonesia. (6th July 2021) - Wijaya Mulya, Teguh; Salvi, Francesca; Gorczynski, Paul; Wells Brown, Tanya
Abstract: Complementing studies on youth mental health that were mainly depoliticised, this article offers a discursive examination of youth mental health in an Indonesian educational context. We argue that subject positions enabled by the discourse of mental health were at odds with dominant constructions of an ideal Indonesian citizen. Drawing upon qualitative data from 22 teachers and 20 students in a junior high school in Indonesia and analyses of educational policies and textbooks, we identified three discourses underpinning the ideal(ised) constructions of young Indonesian citizen, namely, neoliberalism, (masculine) patriotism and (religious) moralism and discussed how these inhibited youth mental health.